Hifz huquq al-tifl fi al-Islam halat al-harb : al-tifl al-Filastini namudhajan = Protection of children rights in Islam during war : a case study Palestinian children / Ahmad Sami al-Qudsi - al-Qudsi, Ahmad Sami (2009)
This research intends to show that Islam has maintained the rights of the children at the time of war religiously, mentally, and physically. The study depended in collecting the information on conducting interviews with MPs and officials in the Palestinian ministries, an official from UNRWA, administrators, school and camps headmasters, eyewitnesses, and children. In order to achieve the desired results the study relied on the descriptive, historical, and analytical method, with the help of the scientific research instruments. Finally, the research showed that, Islam has maintained the rights of the Palestinian children at the time of war, and manifested that, what is happening in Palestine, is a genuine violation of the rights of the children.